Baohuoside I Inhibits Osteoclastogenesis and Protects Against Ovariectomy-Induced Bone Loss - Ma, Min; Fan, Ao-yuan; Liu, Zheng; Yang, Li-qing; Huang, Jun-ming; Pang, Zhi-ying; Yin, Feng (Frontiers in Pharmacology, 2022)
Bone-resorbing osteoclasts are essential for skeletal remodelling, and the hyperactive formation and function of osteoclasts are common in bone metabolic diseases, especially postmenopausal osteoporosis. Therefore, regulating the osteoclast differentiation is a major therapeutic target in osteoporosis treatment. Icariin has shown potential osteoprotective effects. However, existing studies have reported limited bioavailability of icariin, and the material basis of icariin for anti-osteoporosis is attributed to its metabolites in the body. Here, we compared the effects of icariin and its metabolites (icariside I, baohuoside I, and icaritin) on osteoclastogenesis by high-content screening followed by TRAP staining and identified baohuoside I (BS) with an optimal effect. Then, we evaluated the effects of BS on osteoclast differentiation and bone resorptive activity in both in vivo and in vitro experiments. In an in vitro study, BS inhibited osteoclast formation and bone resorption function in a dose-dependent manner, and the elevated osteoclastic-related genes induced by RANKL, such as NFATc1, cathepsin K, RANK, and TRAP, were also attenuated following BS treatment. In an in vivo study, OVX-induced bone loss could be prevented by BS through interrupting the osteoclast formation and activity in mice. Furthermore, mechanistic investigation demonstrated that BS inhibited osteoclast differentiation by ameliorating the activation of the MAPK and NF-kB pathways and reducing the expression of uPAR. Our study demonstrated that baohuoside I could inhibit osteoclast differentiation and protect bone loss following ovariectomy.